Clottable Protein in Limulus: Its Localization and Kinetics of Its Coagulation by Endotoxin - Levin, J; Bang, F. B (Thrombosis and Haemostasis, 1968)
When blood is withdrawn from Limulus, the horseshoe crab, a cellular clot composed of amebocytes quickly forms. Amebocytes are the only type of cell in Limulus blood. During coagulation, Limulus amebocytes undergo morphological changes that are strikingly similar to those seen when mammalian platelets undergo aggregation and viscous metamorphosis. The clottable protein in Limulus blood is derived entirely from amebocytes, and gelation does not require extracellular factors. Cell free Limulus plasma is incoagulable. The cellular localization of clottable protein in Limulus blood provides a precedent for the presence of fibrinogen in mammalian platelets.The clottable protein in lysates of amebocytes has a spectral absorption pattern with a maximum at 270-275 mμ, appears to have a low sedimentation coefficient, is stable at –20° C for 1 week, and is destroyed by heating at 56° C for 30 min. The protein gels upon exposure to endotoxin; and the rate of gelation is related to the concentration of endotoxin but is independent of the concentration of protein in the range tested. The kinetics of this reaction are consistent with the concept that an enzymatic system mediates the conversion of the cellular protein into a gel by endotoxin. Increase in light scattering during the reaction detects as little as 0.004 μg of E. coli endotoxin/ml. This conversion will perhaps provide insight into one of the biological activities of endotoxins.